Does inter-limb asymmetry matter in adolescent speed skaters? - Jin, Zhiyong; Wang, Yufeng; Zhao, Binjie; Bi, Gengchao; Diao, Yuzi; Zhang, Yao; Yan, Li (Frontiers in Physiology, 2025)
Inter-limb asymmetry (IA) has been shown to impact athletic performance, but its relationship with speed skating performance is not yet clear. To investigate the effect of IA in lower limb strength on skating time in adolescent speed skaters, 17 male adolescent speed skaters (age: 16.65 ± 0.79 years, height: 176.63 ± 6.45 cm, weight: 63.08 ± 9.51 kg) underwent body composition, isokinetic knee strength, multi-direction (vertical, horizontal and lateral) single-leg squat jump and single-leg drop jump tests (from a 20 cm box) at the end of the season to assess the IA. The results showed that most lateral single-leg squat jump (LSJ) related variables such as relative lateral peak force (7.40 ± 0.67 N/kg vs 7.03 ± 0.61 N/kg, P < 0.001, ES = 1.32), relative lateral impulse (Imp-L) (2.67 ± 0.23 Ns/kg vs 2.45 ± 0.24 N/kg, P = 0.043, ES = 0.94) and take-off velocity (2.81 ± 0.20 m/s vs 2.59 ± 0.30 m/s, P = 0.001, ES = 0.83) showed a significant left-sided dominance, and increased corresponding asymmetry prolonged 100m and 500 m skating times. Furthermore, increased asymmetry in single-leg vertical drop jump (VDJ) height also prolonged 100 m skating time. For adolescent speed skaters, the LSJ and VDJ tasks exhibit good sensitivity to the lower limb strength asymmetry, and increases in corresponding asymmetries may have negative effects on speed skating performance.